Awareness of takaful among staff in Raub District Islamic Religious Office Pahang / Muhammad Irfan Imaduddin Azran - Azran, Muhammad Irfan Imaduddin (2025)
This study focuses on the awareness of Takaful among staff at Raub District Islamic Religious Office Raub, highlighting its significance as a Shariah-compliant alternative to conventional insurance. Takaful is rooted in the principles of cooperation and risk-sharing, aligning with Islamic values. Despite its growing recognition, challenges persist, including limited understanding, misconceptions, and insufficient training among staff, which hinder its broader acceptance and integration. The objective of this research is to evaluate the level of awareness, analyze the perceived benefits of Takaful over conventional insurance, and propose actionable strategies to improve its adoption. This research employs a qualitative approach, utilizing in-depth interviews with six staff members representing various units within Raub District Islamic Religious Office. Data collection was conducted through structured, face-to-face interviews to gain insights into their perspectives and knowledge of Takaful. The findings indicate that while respondents demonstrate a moderate understanding of Takaful’s concepts, including its Shariah compliance, ethical investment practices, and risk-sharing mechanisms, significant barriers remain. These include the lack of targeted educational initiatives, limited promotional efforts, and misconceptions about its advantages compared to conventional insurance. The study concludes that structured awareness campaigns and comprehensive training programs are essential to bridging these gaps. By fostering a deeper understanding of Takaful’s benefits and its alignment with Islamic principles, the adoption of Takaful can be significantly enhanced. Additionally, collaboration between financial institutions, religious authorities, and community leaders is recommended to promote Takaful as a viable financial solution. This research provides a foundation for future studies to explore Takaful awareness in different contexts and propose innovative methods for increasing its acceptance.